On the Cluj-Ilmenau index of a family of Benzenoid systems. (17th August 2020) - Mohammed, Mohanad A.; AL-Mayyahi, Suad Younus A; Farahani, Mohammad Reza; Alaeiyan, Mehdi
Abstract: Let G be a simple connected molecular graph, with the vertex set and edge set denoted by V ( G ) and E ( G ) respectively, in which the vertices correspond to the atoms while the edges to the bonds of a covalently bonded molecule. The "Omega" Ω( G, x ) polynomial was defined by Diudea on the ground of quasi-orthogonal cut "qoc" edge strips. The Cluj-Ilmenau index CI ( G ) is defined on the above polynomial. In this study, we compute the Cluj-Ilmenau index of a family of Benzenoid Systems named: the Jagged-rectangle B a, b (∀ a, b ∈N).